Research progress in detection method for bisphenol A in food packaging materials - MA Yuqing; DUAN Wanli; PENG Lei; GENG Bingjie; TANG Lingxuan; WANG Haoneng; GAO Fangyuan (Shanghai yufang yixue, 2023)
As an industrial chemical， bisphenol A is widely used in various food packaging materials. However， it is an endocrine disrupting chemical， which has estrogen activity and can cause certain damage to humans. So far， there are few studies on the detection of bisphenol A in self-heating food packaging materials， and there remains a lack of relevant standard. Therefore， it is necessary to establish a simple， sensitive and efficient method for the detection of bisphenol A in self-heating food. This study briefly introduces the pretreatment methods of bisphenol A， such as ultrasonic extraction， solid phase extraction， accelerated solvent extraction， and detection methods， such as gas chromatography-mass spectrometry， high performance liquid chromatography， fluorescent detection， and electrochemical detection.